Hardware and Software Methods for Secure Obfuscation and Deobfuscation: An In-Depth Analysis - Khaled Saleh; Dirar Darweesh; Omar Darwish; Eman Hammad; Fathi Amsaad (Computers)
The swift evolution of information technology and growing connectivity in critical applications have elevated cybersecurity, protecting and certifying software and designs against rising cyber threats. For example, software and hardware have become highly susceptible to various threats, like reverse engineering, cloning, tampering, and IP piracy. While various techniques exist to enhance software and hardware security, including encryption, native code, and secure server-side execution, obfuscation emerges as a preeminent and cost-efficient solution to address these challenges. Obfuscation purposely converts software and hardware to improve complexity for probable adversaries, targeting obscure realization operations while preserving safety and functionality. Former research has commonly engaged features of obfuscation, deobfuscation, and obfuscation detection approaches. A novel departure from conventional research methodologies, this revolutionary comprehensive article reviews these approaches in depth. It explicates the correlations and dynamics among them. Furthermore, it conducts a meticulous comparative analysis, evaluating obfuscation techniques across parameters such as the methodology, testing procedures, efficacy, associated drawbacks, market applicability, and prospects for future enhancement. This review aims to assist organizations in wisely electing obfuscation techniques for firm protection against threats and enhances the strategic choice of deobfuscation and obfuscation detection techniques to recognize vulnerabilities in software and hardware products. This empowerment permits organizations to proficiently treat security risks, guaranteeing secure software and hardware solutions, and improving user satisfaction for maximized profitability.